Self Determination Development in Multicultural Society - Suryana, Dodi (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2018)
The aim of this study is to describe analytically multicultural self-determination. The scope of this study includes: 1) a description of the multicultural self-determination of students formed through the educational process; 2) description of the way or style of regulation based on the high or low self-determination in the cultural domain. The method used was descriptive with crossectional survey design with a sample of first semester students at UPI Bandung using a multi stage cluster sampling technique. Power collection tools in the form of questionnaires, guidelines for observation and interviews. The results of the student research were at the level of identified regulation and the connectivity aspect was the lowest in all aspects of self-determination.